1987
DOI: 10.1111/j.1476-5381.1987.tb11378.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theophylline, choleragen and loperamide on rabbit ileal fluid and electrolyte transport in vitro

Abstract: 1The effects of theophylline and cholera toxin on water and anion movements across rabbit ileum in vitro and the reversal of these effects by the opiate action of loperamide have been investigated. Water movement across the mucosal and serosal surfaces of the tissue was measured continuously by a high resolution method. 2 Theophylline caused an increase in short circuit current and reversed the direction of net Cl1 movement, due mainly to a decrease in mucosal-serosal flux. It also caused a rapid, but transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…We have proposed that small intestinal fluid secretion in vitro is observed when net fluid outflow via intercellular junctions induced by interstitial hydrostatic pressure, exceeds the absorptive flow across the mucosal surface, induced by transcellular and transjunctional osmotic pressure (Ahsan, Ilundain, Naftalin, Sandhu & Smith 1987;Ahsan, Naftalin & Smith, 1988). The presence of a layer of contractile myofibroblasts immediately subjacent to colonic mucosal epithelium could generate this flow in colon (Joyce, Haire & Palade, 1987).…”
mentioning
confidence: 99%
“…We have proposed that small intestinal fluid secretion in vitro is observed when net fluid outflow via intercellular junctions induced by interstitial hydrostatic pressure, exceeds the absorptive flow across the mucosal surface, induced by transcellular and transjunctional osmotic pressure (Ahsan, Ilundain, Naftalin, Sandhu & Smith 1987;Ahsan, Naftalin & Smith, 1988). The presence of a layer of contractile myofibroblasts immediately subjacent to colonic mucosal epithelium could generate this flow in colon (Joyce, Haire & Palade, 1987).…”
mentioning
confidence: 99%
“…Several studies published in the 1980s showed LOP, a “classical” antidiarrheal agent, to exert antisecretory effects . It was suggested that the antisecretory action of LOP is mediated via opioid receptors, either distal to or separate from the adenylyl cyclase and cAMP pathway .…”
Section: Discussionmentioning
confidence: 99%
“…2-6). However, it remains unresolved whether loperamide is capable of eliciting these effects by direct interaction with epithelial cells or whether mediation by subepithelial structures is necessary (3,5,7,8,11). Furthermore, it is an open question whether the antisecretory properties of loperamide are mediated by a naloxonesensitive action on intestinal opiate receptors (2,4,8,22,23) or by a receptor-independent non-opioid effect (5,10,11).…”
Section: Direct Antisecretory Action Of Loperamidementioning
confidence: 98%
“…In respect of the mediation pathway of loperamide's antisecretory action, con icting results have been reported. Several authors have described a naloxone-sensitive action on neurons of the ENS (3,7,8), leading to the conclusion that the antidiarrhoeal action of loperamide is fully accounted for by its opiate agonist action on the submucosal plexus (9). However, in addition to its opioid properties, loperamide has also been found to inactivate calmodulin-regulated phosphodiesterase (10), and a positive correlation between mucosal calmodulin binding of loperamide and its antidiarrhoeal activity has been observed (11).…”
mentioning
confidence: 90%
See 1 more Smart Citation